Spiritual dimension of a world-class murabbis - Samsudin, Sofiah; Zainan Nazri, Nurul Jannah; Hasbullah, Nurul Fadzlin (Islamic Book Trust, 2024)
This chapter is designed to empower the Murabbis and to enhance their spiritual levels and Īmān (Faith) while effectively engaging in the three interconnected aspects which are the Īmān (faith), ‘Ibādah (worship), and Da‘wah (Introducing Islam). By strengthening their connection with Allah, enhancing their worship practices, and improving their skills in conveying the message of Islam, Murabbis will increase their effectiveness in assisting fellow individuals and making a more substantial contribution to the betterment of society.